The role of project management office in managing project portfolio management: A descriptive study in Indonesian banks - Mohammad Ichsan; Mohammad Hamsal; Sri Bramantoro Abdinagoro (Global Business & Finance Review (GBFR), 2023)
Purpose: This paper presents a preliminary study of the complete research to explore how strategic initiatives are implemented in Indonesian banks. It has the aim to descriptively compare the Project Portfolio Management (PPM) Capabilities and bank performance between banks that are applying Project Management Office (PMO) practices and not. Design/methodology/approach: Empirical research has been performed through a survey using questionnaires to define the contribution of formal project management office practices in managing strategic initiatives in Indonesian banks. The data from 82 banks from a total of 115 banks in Indonesia based on the list of Indonesian Financial Authority were collected and analyzed using descriptive analysis with help of statistical tools SPSS 22. Findings: As a preliminary stage, this paper found that banks with formal project management office practices tend to be more effective in managing their strategic initiatives. Research limitations/implications: However, further analysis still needs to be performed to explore how project PPM capabilities and PMO practices influence the bank's performance positively. Originality/value: This study introduces how the project management office and project portfolio management practices in Indonesian Banks at glance and how its comparison those with and without project management practices.
Keywords: 650; Dynamic capabilities; Firm performance; Indonesian banks; Project management office; Project portfolio management